Freeze concentration of pineapple juice - Enerio, Christianne Ramoso (1999)
This study was conducted to evaluate the suitability of freeze concentration as a method of recovering the sugars in the form of concentrated syrup from pineapple juice without resulting in degradation of its components. Based on the results, freezing 2-kg pineapple juice for 22 hours at -5°C (setting No. 1 of a 7 cu ft General Electric upright freezer) was suitable for recovering 1082.7 grams of 22°Bx syrup after 65 minutes of thawing at room temperature. The freezing container used was a 3-liter capacity, cylindrical plastic vessel with 0.05 cm thickness. The freezing capacity of the freezing apparaths was 0.0045°C/min. The physico-chemical properties of the recovered syrup were: soluble solids, 25°Bx; total solids, 28.04%; moisture, 71.96% wet basis; water activity, 0.91; pH, 4.93; titratable acidity (as % citric acid), 0.971; Brix-to-acid ratio, 2.57; and color range, between 2.25YR 2.80/1.69 - 3.58YR 2.78/2.02. The recovered syrup proved suitable as base for pineapple jelly with ι-carrageenan as gelling agent. Results of ANOVA (α = 0.05) for difference among mean scores for sensory attributes of pineapple jelly due to varying amounts of ι-carrageenan and soluble solids showed that the product containing 50°Bx of soluble solids and 0.7% ι-carrageenan was most acceptable.